The locality of the “global village” in the aspect of communication: Pro et contra m. McLuhan - Barevičiūtė, Jovilė (Creativity Studies, 2010)
The article deals with the concept of a “global village” in the aspect of communication. In the first part of the article this concept is introduced without undertaking any judgments and following a position of a judicial researcher. In the second part the conditions of the possibility of a “global village”, regarding the crucial differences of globality and villagicity and their incompatibility, are questioned. A thought is raised whether M. McLuhan’s “global village”, which is constituted by contemporary information and communication technologies and treated as new media, should be assessed as a “global city”, attaching to globality some essentially new and unaccustomed meanings, inspired by the traditional socio‐cultural structural transformations to the networkful nonstructural systems. „Globaliojo kaimo“ lokalumas komunikaciniu aspektu: pro et contra M. Mcluhanui Santrauka. Straipsnyje komunikaciniu aspektu tiriama M. McLuhano „globaliojo kaimo“ samprata. Pirmoje jo dalyje ši samprata pristatoma nesiimant jokių jos vertinimų ir laikantis bešališkos tyrėjo pozicijos. Antroje straipsnio dalyje kvestionuojamos „globaliojo kaimo“ galimybės sąlygos dėl esminių globalumo ir kaimiškumo skirtumų bei jų tarpusavio nesuderinamumo. Išsakoma mintis, kad McLuhano įžvelgiamas „globalusis kaimas“, kurį jo mąstymo perspektyvoje steigia dabartinės informacijos ir komunikacijos technologijos, traktuojamos kaip naujosios medijos, turėtų būti traktuojamas kaip „globalusis didmiestis“, globalumui suteikiant iš esmės naujų ir neįprastų konotacijų, inspiruotų tradicinių sociokultūrinių struktūrų transformacijų į tam tikras tinkliškas bestruktūres sistemas. Reikšminiai žodžiai: dabartinės informacijos ir komunikacijos technologijos (medijos), didmiestis, „globalusis kaimas“, globalusis visetas, tinklas. First published online: 10 Feb 2011